Ideology and Theatre Translation in Contemporary Turkish Theatre - Bozkurt Jobanputra, Seyhan; Zeki Giritli, Mehmet (Vertimo studijos, 2023)
This paper aims to explore the relationship between drama translation and ideology in contemporary Turkish theatre. After delineating the distinction between state/city theatres and independent (private/alternative) theatres, it will then focus on the 2000s with a special emphasis on the translation activities of independent (private/alternative) theatres. In particular, it shall draw attention to how actor/director translators working with or for these theatres have become significant cultural agents and have challenged the status quo by either choosing to translate plays with provocative content or by retranslating plays that were forced to undergo (self-)censorship. The paper will also challenge the general impression in the Turkish context that the reason for retranslating classical plays into Turkish is merely a need to follow and reflect contemporary changes in the language.